Fasudil alleviates brain damage in rats after carbon monoxide poisoning through regulating neurite outgrowth inhibitor/oligodendrocytemyelin glycoprotein signalling pathway. Issue 2 (21st April 2019) - Wang, Li; Xu, Jianghua; Guo, Dadong; Zhou, Xudong; Jiang, Wenwen; Wang, Jinglin; Tang, Jiyou; Zou, Yong; Bi, Mingjun; Li, Qin
Abstract: Carbon monoxide (CO) poisoning can lead to many serious neurological symptoms. Currently, there are no effective therapies for CO poisoning. In this study, rats exposed to CO received hyperbaric oxygen therapy, and those in the Fasudil group were given additional Fasudil injection once daily. We found that the escape latency in CO poisoning group (CO group) was significantly prolonged, the T 1 / T total was obviously decreased, and the mean escape time and the active escape latency were notably extended compared with those in normal control group (NC group, P  < 0.05). After administration of Fasudil, the escape latency was significantly shortened, T 1 / T total was gradually increased as compared with CO group (>1 week, P  < 0.05). Ultrastructural damage of neurons and blood‐brain barrier of rats was serious in CO group, while the structural and functional integrity of neuron and mitochondria maintained relatively well in Fasudil group. Moreover, we also noted that the expressions of neurite outgrowth inhibitor (Nogo), oligodendrocyte‐myelin glycoprotein (OMgp) and Rock in brain tissue were significantly increased in CO group, and the elevated levels of the three proteins were still observed at 2 months after CO poisoning. Fasudil markedly reduced their expressions compared with those of CO group ( P  < 0.05). In summary, the activation of Nogo‐OMgp/Rho signalling pathway is associated with brain injury in rats with CO poisoning. Fasudil can efficiently down‐regulate the expressions of Nogo, OMgp and Rock proteins, paving a way for the treatment of acute brain damage after CO poisoning.